1997
DOI: 10.5558/tfc73107-1
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of conifer release alternatives on songbird populations in northwestern Ontario

Abstract: The effects of conifer-release alternatives on songbird densiLes effets du dtgagement des conifires sur les densitis ties (determined by territory mapping, mist netting, and banding) d'oiseaux chanteurs I d i t m i n t s par la cartographie du terriin four yomg (four to m y e a r old) spruce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…However, as would be expected, foliar arthropods were less abundant (although not statistically so) during that time in herbicide-treated sites than in older naturally regenerated sites and brushsaw-cut plantations. Kostyk et al (1997) and Woodcock (1997) examined the responses of defoliating insects to several conifer release alternatives. Kostyk et al (1997) found that many of the planted conifers, examined two years after treatment, were lightly defoliated by the yellowheaded spruce sawfly (Pikonema alaskensis) and eastern spruce budworm (Choristoneura fumiferana).…”
Section: Terrestrial Invertebrates (Table 2)mentioning
confidence: 99%
See 4 more Smart Citations
“…However, as would be expected, foliar arthropods were less abundant (although not statistically so) during that time in herbicide-treated sites than in older naturally regenerated sites and brushsaw-cut plantations. Kostyk et al (1997) and Woodcock (1997) examined the responses of defoliating insects to several conifer release alternatives. Kostyk et al (1997) found that many of the planted conifers, examined two years after treatment, were lightly defoliated by the yellowheaded spruce sawfly (Pikonema alaskensis) and eastern spruce budworm (Choristoneura fumiferana).…”
Section: Terrestrial Invertebrates (Table 2)mentioning
confidence: 99%
“…While documenting songbird responses to the same alternative treatments, Woodcock (1997) and Woodcock et al (1997) documented abundance of defoliating insects in the regenerating spruce. Two years after release treatments, spruce budworm biomass (g/tree) was greater in spruce trees growing on control plots than in brushsaw-cut or herbicide-treated plots.…”
Section: Terrestrial Invertebrates (Table 2)mentioning
confidence: 99%
See 3 more Smart Citations